Wind Energy Conversion System Based on DFIG with Three-Phase Series Grid Side Converter and Single DC-Link - Ítalo A. Cavalcanti de Oliveira; Cursino Brandao Jacobina; Nady Rocha (Eletrônica de Potência)
In this paper, a wind energy conversion system based on doubly-fed induction generator with an additional series grid side converter without transformer is proposed. Stator voltages may be compensated by series grid side converter under distorted and unbalanced grid voltage sags, thus avoiding over-current in the rotor, over-voltage in the dc-link, double-frequency oscillations in the electromagnetic torque, and rotor over-speed. Moreover, the control strategy of the proposed system allows reactive power to be injected during voltage sags. Simulation and experimental results are presented to evaluate the proposed system.